ASIDOLISIS ENZIMATIK MINYAK IKAN TUNA( THUNNUS THYNNUS) MENJADI PRODUK ASAM LEMAK KAYA OMEGA-3 DENGAN PEMANFAATAN LIPASE GETAH PEPAYA (carica papaya latex) - Wahyuningsih Wahyuningsih; Isti Pudjihastuti; Heny Kusumayanti (METANA, 2012)
ABSTRACT Incorporation of omega-3 polyunsaturated acids (n-3 PUFA) into Tuna (Thunnus thynnus) fish oil was investigated by using acidolysis enzimatis Process. The product of this modification is expected to be used as an ingredient nutrifition food products, especially in milk and baby food as well as pregnant and lactating The purpose of this study was to optimizing the used of lipased papaya latex (Carica papaya latex) in the product to incorporation fatty acids rich in omega-3.Bioreactor acidolysis enzematik development and Optimization of process the productivity of fatty acids rich in omega-3. Reaction Acidolysis was conducted between tuna (thunnus thynnus) fish oil by microbial lipase (5% of the weight of the substrate mixture) or vegetable lipased (Carica papaya latex) (6-10% by weight subtract mixture) as biocatalist.Acidolysis mixture the bioreactor at 40 o C for (2-6 hours) and the stirring speed of 200 rpm, pH (4.5 to 6.5). to eliminate free fatty acids from the product acidolysis performed neutralization with NaOH The results are expected to show that the lipase papaya latex (Carica papaya latex) can be used as biocatalyst incorporated omega-3 fatty acids in   tunaIthunnus thunnyl) fish oil . In this study sought conditions for optimum incorporation rate, ie the use of papaya latex lipase concentration of 8%, the ratio of concentrations of omega-3 fatty acid and palm oil (1:1), pH = 5.5, Optimal time of 4 hours and the temperature (40oC) . The results were analyzed incorporation of omega-3 (EPA and DHA) with GC.EPA generated: 3.57% and DHA = 3.91% Key word:Acidolysis,Tuna fish oil